2021
DOI: 10.1159/000516192
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Coenzyme Q10 Combined with Aescin Protects against Sepsis-Induced Acute Lung Injury

Abstract: Sepsis-associated acute lung injury (ALI) is a critical condition characterized by severe inflammatory response and mitochondrial dysfunction. Coenzyme Q10 (CoQ10) and aescin (AES) are well-known for their anti-inflammatory activities. However, their effects on lipopolysaccharide (LPS)-induced lung injury have not been explored yet. Here, we asked whether combined pretreatment with CoQ10 and AES synergistically prevents LPS-induced lung injury. Fifty male rats were randomized into 5 groups: (1) control; (2) LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…After reviewing all of the publications, 10 studies were excluded because of missing outcome data ( Ehrhart et al, 2000 ; Tawadros et al, 2007 ; Nader and Baraka, 2012 ; An et al, 2014 ; Wang et al, 2015 ; Liu and Chen, 2016 ; Shen et al, 2017 ; Ni et al, 2019 ; Wang et al, 2019 ; Yang et al, 2019 ), and another 12 studies were excluded because multiple interventions were investigated ( Murakami et al, 2000 ; Lin et al, 2011 ; Li et al, 2014b ; Li et al, 2016a ; Li et al, 2016b ; Baradaran Rahimi et al, 2019 ; Ye et al, 2019 ; Duan et al, 2020 ; Yue et al, 2020 ; Choi et al, 2021 ; Zhang et al, 2021 ; Liu et al, 2022 ). In conclusion, 16 studies were included in this meta-analysis, as described below ( Shi et al, 2007 ; Yang et al, 2011 ; Chen et al, 2014 ; Yang et al, 2014 ; Yuan et al, 2014 ; Wei and Wang, 2017 ; Li et al, 2018a ; Li et al, 2018b ; Luo et al, 2019 ; Ren et al, 2019 ; Zhang et al, 2020 ; Ali et al, 2021 ; Dikmen et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Wu et al, 2021 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After reviewing all of the publications, 10 studies were excluded because of missing outcome data ( Ehrhart et al, 2000 ; Tawadros et al, 2007 ; Nader and Baraka, 2012 ; An et al, 2014 ; Wang et al, 2015 ; Liu and Chen, 2016 ; Shen et al, 2017 ; Ni et al, 2019 ; Wang et al, 2019 ; Yang et al, 2019 ), and another 12 studies were excluded because multiple interventions were investigated ( Murakami et al, 2000 ; Lin et al, 2011 ; Li et al, 2014b ; Li et al, 2016a ; Li et al, 2016b ; Baradaran Rahimi et al, 2019 ; Ye et al, 2019 ; Duan et al, 2020 ; Yue et al, 2020 ; Choi et al, 2021 ; Zhang et al, 2021 ; Liu et al, 2022 ). In conclusion, 16 studies were included in this meta-analysis, as described below ( Shi et al, 2007 ; Yang et al, 2011 ; Chen et al, 2014 ; Yang et al, 2014 ; Yuan et al, 2014 ; Wei and Wang, 2017 ; Li et al, 2018a ; Li et al, 2018b ; Luo et al, 2019 ; Ren et al, 2019 ; Zhang et al, 2020 ; Ali et al, 2021 ; Dikmen et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Wu et al, 2021 ) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Rats ranged in age from 6 to 8 weeks and in weight from 90 to 350 g. In terms of intervention, diterpenoid, monoterpenoid, sesquiterpenoid, and triterpenoid were used in seven studies ( Shi et al, 2007 ; Yang et al, 2011 ; Yang et al, 2014 ; Wei and Wang, 2017 ; Li et al, 2018a ; Li et al, 2018b ; Luo et al, 2019 ), three studies ( Yuan et al, 2014 ; Ren et al, 2019 ; Li et al, 2021 ), two studies ( Ali et al, 2021 ; Wang et al, 2021 ), and four studies ( Chen et al, 2014 ; Zhang et al, 2020 ; Dikmen et al, 2021 ; Wu et al, 2021 ), respectively. In addition, 13 studies used male rats ( Shi et al, 2007 ; Yang et al, 2011 ; Chen et al, 2014 ; Yang et al, 2014 ; Yuan et al, 2014 ; Wei and Wang, 2017 ; Li et al, 2018a ; Luo et al, 2019 ; Ren et al, 2019 ; Zhang et al, 2020 ; Dikmen et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ), whereas three studies did not report gender ( Li et al, 2018b ; Ali et al, 2021 ; Wu et al, 2021 ). Sprague Dawley rats were used in 11 studies ( Shi et al, 2007 ; Yang et al, 2014 ; Wei and Wang, 2017 ; Li et al, 2018a ; Li et al, 2018b ; Luo et al, 2019 ; Ren et al, 2019 ; Ali et al, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Wu et al, 2021 ) and Wistar rats in five studies ( Yang et al, 2011 ; Chen et al, 2014 ; Yuan et al, 2014 ; Zhang et al, 2020 ; Dikmen et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that the p38 mitogen-activated protein kinase (MAPK) signaling pathway is closely related to the lung injury [10][11][12] . This study was designed to investigate the effects of propofol on inflammatory response and activation of p38 MAPK signaling pathway in rats with VALI.…”
Section: Introductionmentioning
confidence: 99%